2019
DOI: 10.1080/02656736.2019.1679895
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia with photon radiotherapy is thermoradiobiologically analogous to neutrons for tumors without enhanced normal tissue toxicity

Abstract: The depth dose profiles of photons mirror those of fast neutrons. However, in contrast to the high linear energy transfer (LET) characteristics of neutrons; photons exhibit low LET features. Hyperthermia (HT) inhibits the repair of radiation-induced DNA damage and is cytotoxic to the radioresistant hypoxic tumor cells. Thus, thermoradiobiologically, HT simulates high LET radiation with photons. At temperatures of 39-45 C, the physiological vasodilation allows rapid heat dissipation from normal tissues. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
(125 reference statements)
0
7
0
Order By: Relevance
“…These magnetic nanoparticles in the presence of alternating magnetic field could deliver local hyperthermia and with additional payloads could act as "nanobullets." The figure has been reproduced and modified with permission from Datta et al (212,213).…”
Section: Strengths: Online and Non-invasive Thermometry Treatment Planning And Controlmentioning
confidence: 99%
“…These magnetic nanoparticles in the presence of alternating magnetic field could deliver local hyperthermia and with additional payloads could act as "nanobullets." The figure has been reproduced and modified with permission from Datta et al (212,213).…”
Section: Strengths: Online and Non-invasive Thermometry Treatment Planning And Controlmentioning
confidence: 99%
“…Radiotherapy (RT) is supposedly a curative treatment modality, but the radiation dose required to eradicate all cancer cell subpopulations in a tumour can often not be applied due to severe acute or long-term side effects, which include radiation-induced tissue fibrosis and second malignancies 11 . Hyperthermia is known to be one of the most potent radiosensitisers [12][13][14][15][16] , meaning that less radiation is required to achieve the same local tumour cell kill, thereby reducing the adverse effects of radiation in the adjacent normal tissues, e.g. [17][18][19][20][21] .…”
mentioning
confidence: 99%
“…A number of phase III randomized trials, pairwise meta-analyses and network meta-analyses have shown the efficacy of HT in a wide range of malignancies [7,8,20,[32][33][34][35][36]. Thermoradiobiologically, HT with photons is analogous to that of neutrons but devoid of any added acute or late morbidity while with protons it mimics 12 C beam therapy [37][38][39][40]. In phase III randomized study, HT with CT has improved survival outcomes in soft tissue sarcoma [41].…”
Section: Discussionmentioning
confidence: 99%